Melioidosis: Important Neglected Zoonosis and Their Presence in Animal in Indonesia, Handling Constraints and Solutions - Tati Ariyanti; Susan M Noor (Indonesian Center for Animal Research and Development, 2022)
Melioidosis is a zoonosis caused by the bacterium Burkholderia pseudomallei, a saprophyte bacteria that is widely found in the environment. This bacteria causes Melioidosis in various animal species with clinical manifestations vary depending on species, but generally fever, depression, weight loss, respiratory sign, lameness, swelling of the joints, and potentially death. The incidence of Melioidosis in humans has been widely reported in many countries and it is estimated that every year there are 20,038 cases with a mortality rate of 51%. In contrary, there have not been many reports of Melioidosis in animals in the world, due to Melioidosis is not well known, limited diagnostic techniques and laboratory facilities in identifying the disease correctly. The presence of Melioidosis in animals and humans has been reported in Indonesia but the incidence is not yet known. This paper discusses Melioidosis in animals, etiological agent, epidemiology, modes of transmission, clinical manifestations, diagnosis and prevention and their presence in animals in Indonesia and constraints and solutions.